Práticas informacionais terapêuticas e a resiliência informacional - Sousa, Laiana Ferreira de (2022)
The theme addressed in this research is part of the symbolic universe of social reading practices, especially with regard to the practical aspects of obtaining information through literature, with a view to developing informational resilience. The general objective of this research is to understand how reading mediation practices developed in online environments, through Bibliotherapy, can contribute to the informational resilience of children who go through the collectivized grief caused by the Covid-19 pandemic. Thus, in this way, approaching Bibliotherapy as a multidisciplinary resource that helps therapeutically through the dialogic and collaborative process of reading mediation on virtual videoconferencing platforms. In the informational field, the bibliotherapeutic process is considered a strategy for the development of socio-emotional skills in life contexts in which uncertainties are limiting aspects. In this sense, this research presents the concept of Therapeutic Informational Practices to explain the informational process that results from reading practices developed from Bibliotherapy in the educational context, permeated by the collectivized mourning caused by the new Coronavirus pandemic. The pandemic was and is being the scene of many losses, whether symbolic losses linked to changes and restrictions on life in society or loss due to death. It starts from the assumption that reading practices, understood here as promoters of therapeutic informational practices, since they are fundamentally processed as mediators of informational content, adapted to the reality of the subjects to whom they are intended, can be configured as an important element capable of offering these subsidies necessary for them to overcome a state of informational uncertainty and build a situation of informational resilience capable of re-signifying constitutive elements of their life contexts. Aware of the complexity of this problem, we chose to use the Brazilian model (2017), in order to explore its explanatory elements of the formation/maintenance of social bonds effected from group interaction and the informational reading practices generated from of Bibliotherapy. From a methodological point of view, an empirical investigation was carried out to collect information through action research and focus groups. Then, the data were transcribed and subsequently subjected to thematic analysis, under the bias of Bardin's content analysis (2011). It is characterized as a study of informational practices of children in the pandemic, from the perspective of the interactionist and socio-emotional approach. The theoretical foundation was built from the dialogue between authors from different areas and brings elements of Humanistic Social Psychology, especially the Person-Centered Approach by Carl Rogers. From the testimonies collected during the focus group, especially the speeches and statements of the children, it was concluded, in this investigation, that the collaborative therapeutic informational practices developed, specifically in the context of interactions mediated by virtual platforms, especially in the childhood phase, can contribute to that children, especially those who go through the grieving process, are able to deal with the uncertainties caused by the loss and develop the capacity for informational resilience.